ANTESEDEN MINAT BELI ULANG PENGGUNA SITUS OLX.CO.ID DI INDONESIA - Prasetyo, Sony Agung; Widiyanto, Ibnu (Faculty of Economics and Business Diponegoro University, 2015)
An easier access of internet tendsto change a lot of new style ofhuman life. This style is an online shopping. OLX is one of the biggest online shopping site in Indonesia that provides an access for the people to buy used or new goods. This research is to analyze the influences of advertising attractiveness and ease of shoppingon consumer trust affecting repurchase intentionat OLX.co.id.A number ofsamples used in this research were 385 respondents, the respondents were anyone whoever shopped at OLX.co.id. The questionnaires were distributed from March 2015 to April 2015 using google drive with chat and email message notices. The analytical technique employedmultiple regression analysis.The results of this research shows that the two of the independent variables have positive and significant influenceson consumer trust. Advertising attractivenesshas bigger influence on consumer trust and an indirect influence on the repurchase intention. This result supports the previous research stating that consumer trust has a significant positive influence on the repurchase intention and has a significant role as an intervening variable.